RhoA targeting by probiotics as strategy to interfere the critical link to major hallmarks of Alzheimer disease / Muhammad Zaki Ramli - Ramli, Muhammad Zaki (2019)
Alzheimer’s disease (AD) is the commonest form of dementia characterised by aggregation of amyloid beta (Aβ) plaque. RhoA, which is being increasingly recognised for its role in AD pathogenesis through the amyloidogenic pathway, may serve as a potential therapeutic target. Preliminary screening of MRS broth fermented with lactic acid bacteria (LAB) yielded strain-dependent inhibition of RhoA activation in vitro. LAB also significantly inhibited Aβ produced by SK-N-SH transfected with amyloid precursor protein (APP) gene. A strong correlation was found between inhibition of RhoA and Aβ. LAB-derived supernatant were also presented with increased organic acids which included lactic acid (>100%), acetic acid (>15.3%), butyric acid (>34.5%) and propionic acid (>29.1%). The findings were validated using lipopolysaccharide (LPS)-challenged rats with neuroinflammation that mimic AD. Sprague Dawley rats (male, 3 months) were divided (n=6/group) into wild-type, control, vehicle controls and treatment groups [109 CFU/ mL LAB6/ Pediococus pentasaceus or LAB12/ Lactobacillus plantarum and 10 mg/kg ibuprofen (positive control) for 31 days]. Except for wild-type, all rats were injected (i.p.) with 0.25 mg/kg LPS for 4 days starting from day 28. The rodents were then subjected to the Morris Water Maze Test. Brains were harvested and subjected to Western Blot, immunohistostaining and biochemical analyses. LAB-fed LPS-challenged rats exhibited significantly (p<0.05) reduced escape latency and escape distance. They remained longer in the platform quadrant (>9.8±0.5 sec) when compared to control (<5.1±1.9 sec). The improved memory was accompanied by significantly (p<0.05) decreased Aβ (<31.4%) and RhoA activity (<22.5%), augmented BDNF (>15.4%) and ACh (>32.3%), reduced AChE (<40.1%) and NO (<30.3%) levels. LAB-fed rats also showed increased IL-10 (>32.1%) and decreased IL-1β (<39.5%). The LAB was then investigated using Aβ-induced rats that mimic Aβ plaque aggregation in AD. Sprague Dawley rats (male, 3 months) were divided (n=7/group) into wild-type, sham, control, vehicle controls and treatment groups. Except for wild type and sham, all rats were subjected to intracranial injection with 5 μg/μL Aβ 1-42 peptide. Treatment groups (day 4) were administered with either 109 CFU/mL LAB6, LAB12 or 10 mg/kg ibuprofen for 30 days. The Aβ-induced rats were assessed for parameters similar to those of LPS-challenged rats. LAB-fed rats exhibited significantly (p<0.05) reduced escape latency, escape distance and remained longer in platform quadrant. The improved memory was accompanied by reduced Aβ (<31.4%) and RhoA activity (<35.7%), increased BDNF (>18.3%) and ACh (>30.3%), reduced AChE (<28.8%) and NO (<33.6%). LAB-fed rats also exhibited up-regulation of IL-10 (>33.3%) and down-regulation of IL-1β (<41.6%). The present findings indicated that LAB-induced neuroprotection could be mediated via inhibition of RhoA-Aβ generated neuroinflammation and accompanied by increased production of organic acid metabolites, restored BDNF, reduced degradation of acetylcholine and down-regulation of pro-inflammatory as well as up-regulation of anti-inflammatory cytokines.